Adjustment with a human face : protecting the vulnerable and promoting growth vol. 1 - Cornia, G.A., ed. (Oxford University P. OxfordGB, 1988)
Describes the recession and adjustment-induced deterioration in the economic circumstances of millions of third world families in the 1980's. Identifies aspects of adjustment which impinge particularly on the poor and also which aspects can serve to protect poor and vulnerable groups. Summarizes 10 case studies on country experience, both on how the position of the poor has changed in recent years and on the nature of the adjustment policies these countries followed. Outlines policy framework for adjustment with a human face including macro and micro policies with respect to growth, production, income generation and in the key areas of employment, education, health and nutrition.